FORMULASI KRIM PENYEMBUH LUKA TERINFEKSI Staphylococcus aureus EKSTRAK DAUN TAPAK KUDA (Ipomoea pes-caprae (L.) Sweet PADA TIPE A/M - The, Falles Raintung; Edy, Hosea Jaya; Supriati, Hamidah Sri (PHARMACON, 2013)
ABSTRACTBeach Morning Glory is a plant that grew around the beach which has purple flower. BeachMorning Glory leaves contains chemical compounds such Flavonoids, Hydroquinonephenolic, alkaloids, and Tannins. Beach Morning Glory leaves has known as the medicine ofacne and furunkulosis that caused by Staphylococcus aureus. The topical product is needed toheal the skin infection. The purpose of this research were to test about physical quality ofcream based and Beach Morning Glory cream extract at the concentration between 2,5 %, 5%, and 7,5%. The result shows the cream base and Beach Morning Glory cream withconcentration of 2,5 %, 5 %, and 7,5 % fulfilled the Organoleptic and Homogenity test butwas not fulfilled in the standart parameter of pH and spreadabillity.Keywords : Ipomoea pes-caprae (L.) Sweet, W/O Cream.